Facing the Truth: New follies in artificial intelligence - A.K.M. Skarpelis (WZB-Mitteilungen: Quartalsheft für Sozialforschung, 2022)
Every human being has a comparatively unique appearance – and can be identified by a picture or recording of them. Automated facial recognition, too, makes use of this circumstance. Because governments and corporations increasingly use these technologies, critics have been vocal about their ethical and political implications. Less frequent are critiques of the technical aspects of facial recognition: Photography still gets a benefit of doubt as a representation of reality. Not only is this confidence no longer warranted in the age of ubiquitous photo manipulation. We also overlook that in artificial intelligence techniques of “racial recognition” have been developed, which create new ethnic categories. These are no less dubious than earlier 19th and 20th century ones.
Keywords: 300